Inclusão de alunos público-alvo da Educação Especial nos anos finais do Ensino Fundamental: redes de colaboração entre professores do ensino comum - Silva, Isalém Angelo Vieira da (2023)
The study aims to establish collaborative actions among teachers in regular education (with the necessary support from those working in Special Education), aiming to reinforce the teaching and learning processes of target students in Special Education enrolled in the 9th-grade of a school in the State Education Network, located in Irupi/ES. It is based on Boaventura de Sousa Santos (2006, 2007, 2008), a theorist who brings a sociological approach to the inquiry, using concepts such as indolent reason, ecology of knowledge, and translation. In addition, within a pedagogical framework, it presents Philippe Meirieu (2002, 2005), discussing the pedagogical moment, didactic tenacity, and solicitude. It is also grounded in authors of Special Education, with a highlight on those dedicated to producing knowledge about collaborative work. It is a qualitative study that assumes collaborative-critical action research as an investigative perspective capable of producing science in the relationship between peers and in collective, participatory, and collaborative construction with participants. The study involved four teachers from the Language and Codes field (Portuguese Language, Physical Education, Art, and English), one special education teacher, and six students supported by this modality of education. Methodologically, it was carried out through the following procedures: data request from the Ministry of Education and the school for production of it; observing the 9thgrade class; moments of planning and mediation of planned actions in the regular classroom, which allowed the work with three didactic sequences that adopted the following generative themes: a) child labor; b) visual chords as expression and identity strengthening; c) folklore. Data were produced from August to December 2022, using field journal, cell phone camera, and a drone as instruments. As results, the research points out the contributions of collaboration among teachers in regular education in the articulation of the regular class with the Special Education services, in reinforcement of collective actions for planning and mediation of pedagogical work, in the dialogue between curricular knowledge and the involvement of students with disabilities and global developmental disorders in the school curriculum, without disregarding the specific learning needs of these individuals.